Unwinding Link between Coronavirus and Diabetes Patient - Bhadauria, Shailendra S.; Malviya, Rishabha; Sharma, Pramod Kumar (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
The COVID-19 illness is a highly contagious disease presently affecting more than 200 countries caused by the SARS-CoV-2 coronavirus (Severe Acute Respiratory Syndrome Coronavirus-2). Persons with diabetes mellitus (DM), severe obesity, cardiovascular disease, and hypertension are more likely to be infected with COVID-19 and are at a higher risk of death. The COVID-19 pandemic is overlapping the preexisting diabetes pandemic to produce fast and very vulnerable groups of COVID-19 and diabetes patients. Evidence relating to COVID-19 and diabetes is less but continues to emerge. In this context, we present evidence identified through rapid reviews. The current manuscript aims to provide information on diabetic patients suffering from COVID-19. Consequently, diabetic people have a higher susceptibility to severe SARS-CoV- 2 infections since defects in the glucose metabolism exacerbate the COVID-19 pathogenesis. After an extensive literature survey, it can come to an end that specific care is required for diabetes patients suffering from the COVID-19 virus. COVID-19 infection in diabetic patients may lead to loss of life if immediate care is not taken. This paper gives insight into the COVID-19 disease complications relevant to diabetes and emphasizes the current information and emerging concepts for SARS-CoV-2 infections in patients with DM.
Keywords: treatment